Anesthetic Management of Patients After Traumatic Injury With Resuscitative Endovascular Balloon Occlusion of the Aorta. (November 2019) - Engdahl, Ashton J.; Parrino, Christopher R.; Wasicek, Philip J.; Galvagno, Samuel M.; Brenner, Megan L.; Anders, Megan G.; Conti, Bianca; Rock, Peter; McCunn, Maureen
Abstract : Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a temporizing maneuver for noncompressible torso hemorrhage. To our knowledge, this single-center brief report provides the most extensive anesthetic data published to date on patients who received REBOA. As anticipated, patients were critically ill, exhibiting lactic acidosis, hypotension, hyperglycemia, hypothermia, and coagulopathy. All patients received blood products during their index operations and received less inhaled anesthetic gas than normally required for healthy patients of the same age. This study serves as an important starting point for clinician education and research into anesthetic management of patients undergoing REBOA.